Design and Prototyping of Power Saving System for Auditorium. - Jakuma, Stephen (Kabale University, 2023)
Power consumption and wastage in the auditorium has the greatest impact financially on the users. This requires serious control using switching circuitry to control the lighting system using occupant sensor monitoring different section occupied. The work in this report emphasizes the need for automated light switching devices for auditorium Chapter One discusses the background of the problem, problem statement, objectives of the research, and its significance. Chapter two discusses the literature review, related research, tools and materials used to carry out the research and building the prototype for proof of concept. Chapter three describes the methods used to achieve the main objective and specific objectives of the research. Chapter four discusses in detail the simulations, experiments, procedure and precautions taken while carrying out the experiments and building the prototype. The results of the experiments, milestones achieved are also discussed in this chapter. The conclusions from this research and recommendations also discussed.